THE SIGNIFICANCE OF FELDMAN METHOD IN ART CRITICISM AND ART EDUCATION - Alashari, Duaa (International Journal of Psychosocial Rehabilitation, 2024)
This paper addresses art criticism, which undoubtedly plays a significant role in enrichingthe art's creative and aesthetic state. The paper aims to identify the steps of art criticism forthe Feldman. Feldman developed a four steps method to be able to interpret, judge andevaluate artistic works. The researcher has carried out this study by focusing on artisticcriticism basics to help guide students to improve and develop their level regarding artisticcriticism. The method used in this study is descriptive and analytical. The study reachedseveral conclusions, among which was that art criticism is an organized series of situations.Feldman method is a process that requires an in-depth analysis of art issues, understandingthe various critical trends, being aware of all artistic developments, artistic achievements,and being aware of the principles and elements of art. The relevance of criticism to art isclosely related because criticism is centred around the work of art, and stems from analysisand distinction.